DIPLOMASI KBRI SEOUL DALAM PROMOSI BUDAYA INDONESIA TAHUN 2021 – 2023 - Nadilla, Raviqa; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
In 2021 - 2023, the Embassy of the Republic of Indonesia (KBRI) in Seoul carried out various strategic efforts to promote Indonesian culture in South Korea. This activity aims to increase the understanding and appreciation of the Korean people towards Indonesia's cultural richness and strengthen bilateral relations between the two countries. Then, this article will try to answer the question of how the Diplomacy Strategy of the Indonesian Embassy in Seoul in the Promotion of Indonesian Culture in 2021 - 2023. The research method used is qualitative by using the theory of public diplomacy with data collection techniques through literature studies have been used. So it aims to know and understand more deeply the Strategy carried out by the Indonesian Embassy in Seoul in the Promotion of Indonesian Culture in 2021 - 2023. The results show that there is a positive impact of various strategic programs carried out by the Indonesian Embassy in Seoul, one example is in 2021 by holding the Gugak Festival, then in 2022 held the Itaewon Global Festival, and in 2023 held the Busan, Ansan, and Seoul Indonesia Festivals. Which has an effect on South Korean tourist visits to Indonesia, which is evident from the surge in the number of Korean tourists to Indonesia which increased from 2021 to 9,497 and in 2023 reached 347,145 people, shows the effectiveness of the multi-dimensional approach of the Indonesian Embassy in Seoul in cultural diplomacy. This success not only strengthens the socio-cultural aspect but also opens up wider opportunities for cooperation in various sectors, proving that cultural diplomacy is an effective soft power instrument Keywords: Indonesian Embassy in Seoul, Cultural Promotion, South Korea, Indonesia.